Ricochet pollination in Senna (Fabaceae) – petals deflect pollen jets and promote division of labour among flower structures. (21st August 2017) - Amorim, T.; Marazzi, B.; Soares, A. A.; Forni‐Martins, E. R.; Muniz, C. R.; Westerkamp, C.
Abstract: Naturalists Fritz and Hermann Müller hypothesised that heteranthery often leads to a division of labour into 'feeding' and 'pollinating' stamens; the latter often being as long as the pistil so as to promote successful pollination on the bees' back. In many buzz‐pollinated species of Senna, however, the so‐called pollinating stamens are short and not level with the stigma, raising the question of how pollen is shed on the bees' back. Here we explore a mechanism called 'ricochet pollination'. We test whether division of labour is achieved through the interaction between short lower stamens and strongly concave 'deflector petals'. We studied the arrangement and morphology of the floral organs involved in the ricochet pollination, functioning of the flowers through artificial sonication and observed the interactions between bees and flowers in the field. The middle stamens are adapted to eject pollen downwards, which can be readily collected on the bee mid legs. Most of the pollen is ejected towards the deflector petal(s). Pollen from this set of stamens is more likely to contribute to pollination. The pollen grains seem to ricochet multiple times against the deflector petals to eventually reach the bee's back. The pollen ricochet mechanism promotes a division of labour by involving additional floral organs, such as petals, reinforcing the Müllers' division‐of‐labour hypothesis. However, alternative, non‐multiexclusive hypotheses could be explored in genus Senna and other angiosperm species.